2018
DOI: 10.1080/13546783.2018.1494630
|View full text |Cite
|
Sign up to set email alerts
|

Moving arms: the effects of sensorimotor information on the problem-solving process

Abstract: Embodied cognition postulates a bi-directional link between the human body and its cognitive functions. Whether this holds for higher cognitive functions such as problem solving is unknown. We predicted that arm movement manipulations performed by the participants could affect the problem-solving solutions. We tested this prediction in quantitative reasoning tasks that allowed two solutions to each problem (addition or subtraction). In two studies with healthy adults (N ¼ 53 and N ¼ 50), we found an effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…Evaluating arithmetic preferences in a purely mathematical task that requires participants to create arithmetic addition or subtraction facts from visually presented components (operands, operators, and results) could be used to avoid this complexity confound. This is illustrated in the study by Werner et al ( 2019 ), which revealed no addition bias but confirmed the well-known sensitivity of operation choices to spatial cues.…”
Section: Insights From Mathematical Cognition Researchsupporting
confidence: 80%
“…Evaluating arithmetic preferences in a purely mathematical task that requires participants to create arithmetic addition or subtraction facts from visually presented components (operands, operators, and results) could be used to avoid this complexity confound. This is illustrated in the study by Werner et al ( 2019 ), which revealed no addition bias but confirmed the well-known sensitivity of operation choices to spatial cues.…”
Section: Insights From Mathematical Cognition Researchsupporting
confidence: 80%
“…5). Again, we find similar embodiment signatures in mathematical cognition, where physical procedures of separation and connection prime subtraction and addition solutions, respectively (Werner & Raab, 2013;Werner, Raab, & Fischer, 2019). Conceptualization of addition/subtraction as connection/separation is also revealed by semantic priming between linguistic expressions defining commonly related entities and additions and by the importance of gestures in math education .…”
Section: Introductionsupporting
confidence: 57%
“…5). Again, we find similar embodiment signatures in mathematical cognition, where physical procedures of separation and connection prime subtraction and addition solutions, respectively (Werner & Raab, 2013; Werner, Raab, & Fischer, 2019). Conceptualization of addition/subtraction as connection/separation is also revealed by semantic priming between linguistic expressions defining commonly related entities and additions (Bassok, Pedigo, & Oskarsson, 2008) and by the importance of gestures in math education (Sinclair & Heyd-Metzuyanim, 2014).…”
supporting
confidence: 54%